Synchrotron X-ray Fluorescence Microscopy Reveals Trace Elemental Indicators of Life History in Marsupial Teeth - William M. G. Parker; Justin W. Adams; David P. Hocking; Erich M. G. Fitzgerald; Geoff Shaw; Marilyn B. Renfree; Alistair R. Evans (Biological Trace Element Research, 2025)
As teeth develop, their mineralised composition is a bio-recorder of diet, environment, and growth. High-resolution elemental mapping provides a tool to reveal records of life history within teeth. The relative concentrations of a range of trace elements change between in utero development, birth, and weaning in eutherian mammals. Marsupials, however, have a different mode of development: altricial birth and growth within the pouch facilitated by compositional transitions in milk. How these differences alter patterns of elemental mineralisation and become recorded in marsupial teeth is previously unknown. This study analyses the distribution of calcium (major element), zinc (actively incorporated trace element), and strontium (passively incorporated trace element) in the teeth of five species of diprotodontian marsupial using synchrotron X-ray fluorescence microscopy. We find that the diprotodontian lower incisor concatenates elemental variation from across the molariform dentition, preserving a prolonged record of life history in four of the five species. Patterns of elemental incorporation in enamel, dentine, and cementum are presented, with Ca, Zn, and Sr having differing distributions. Zn accretion indicates a role in mineralisation and/or prevention of tooth degradation. Zn also demarcates incremental cementum lines. Sr is shown to be passively incorporated into marsupial teeth, with increasing Sr concentration in milk recorded in dental tissues formed contemporaneously. Older individuals have oscillatory signals in Sr that appear linked to seasonality. These findings highlight some similarities between eutherian and marsupial trace element incorporation, particularly in the distribution of Zn. Sr signals in marsupial teeth record key aspects of life history.

Variation in microbial communities colonizing horticultural slow sand filter beds: implications for filter function - Paul J. Hunter; Leo A. Calvo-Bado; Nick R. Parsons; Tim R. Pettitt; Geoff M. Petch; Eve Shaw; J. Alun W. Morgan; John M. Whipps (Irrigation Science, 2013)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Restricted plant species on sub-Antarctic Macquarie and Heard Islands - Dana M. Bergstrom; Perpetua A. M. Turner; Jenny Scott; Geoff Copson; Justine Shaw (Polar Biology, 2006)